Social psychology and health - Stroebe, Wolfgang (Open University Press, 2000)
(Open University Press) Discusses major health topics, such as which behavior patterns are detrimental to health and how people can change their behavior, from a social psychological perspective. Argues for an integrative approach combining psychological, economic, and environmental interventions. Softcover, hardcover also available.
Mapping social psychology
Keywords: sociální psychologie; sociologie; Psychology, Social; psychiatrie